Region and regionalism ¿autonomy or integration? (2004)
The question over identity, autonomy and integration between regions, about the requirement to define politics and aims, still prevails. The Colombian Caribbean region has been characterized in accordance with the nation historical state of affairs; the last attempts procuring a successful Caribbean project have been tinged by bureaucracy and politician slackness. The text evaluates the region performance, regional development politics and its possibilities to improve the current poverty and underdeveloped prospect.